Sex‐discordant twins despite single embryo transfer: a report of two cases - Sugawara, Nobuo (Reprod Med Biol, 2010)
We report two extremely rare cases in which the patients delivered male and female infants that were dizygotic twins (DZT) despite single embryo transfer. Case 1: The patient was a 35‐year‐old woman with a 9‐year history of unexplained infertility. In an oocyte retrieval cycle, one blastocyst was transferred; at 26 weeks of gestation, she delivered a 704‐g female infant and a 420‐g male infant by cesarean section. Because both infants were of extremely low birth weight, they were placed in the neonatal intensive care unit. Congenital anomalies were not found in either infant. Case 2: The patient was a 30‐year‐old woman with a 1‐year history of infertility. Hysterosalpingogram revealed bilateral tubal occlusion. In a frozen/thawed cycle one blastocyst was transferred during her natural ovulation cycle. She achieved a pregnancy and delivered a 2,877‐g female infant and a 2,544‐g male infant at 36 weeks of gestation by cesarean section. The female infant was diagnosed with a neural tube defect. No congenital anomalies were detected in the male infant. We hypothesize that the DZTs might have been the result of concurrent embryo transfer and natural ovulation and intercourse.